2016
DOI: 10.3109/0886022x.2015.1128290
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis is high in chronic kidney disease patients in South East England and drug resistance common

Abstract: The risk of tuberculosis (TB) is significantly increased in chronic kidney disease (CKD). Data on TB in CKD in the UK are sparse; most information stems from countries with high background prevalence. The aim of this study was to estimate the incidence of TB in CKD patients in South East London and to describe the epidemiology, treatment, and outcome. CKD patients with TB between 1994 and 2010 were identified retrospectively. Data were collected on type of renal replacement therapy, the method of TB diagnosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 20 publications
3
19
0
1
Order By: Relevance
“…However, the figures from a large UK renal unit suggest that hemodialyzed patients at risk could well benefit from screening, whether or not they proceed to transplant surgery. 9 In a recent study from Turkey, Sehan et al 20 demonstrated that 6.2% of patients on hemodialysis with a positive QFT result progressed to active disease over a 5 -year follow -up compared with 1.1% of healthy controls.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the figures from a large UK renal unit suggest that hemodialyzed patients at risk could well benefit from screening, whether or not they proceed to transplant surgery. 9 In a recent study from Turkey, Sehan et al 20 demonstrated that 6.2% of patients on hemodialysis with a positive QFT result progressed to active disease over a 5 -year follow -up compared with 1.1% of healthy controls.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%
“…In addition to this, patients on peritoneal dialysis who are at risk of intra -abdominal infection also require special consideration. 9,21 A chest radiograph should be performed as part of the workup of all renal patients to show any evidence of previous TB disease, but also so that future radiographs can be compared with previous studies, and any new infiltrates warrant further investigation. Further site -specific investigations such as abdominal ultrasound, computed tomography, or spinal magnetic resonance imaging should be considered based on symptoms.…”
Section: Tuberculin Skin Testmentioning
confidence: 99%
See 3 more Smart Citations